2020
DOI: 10.1038/s41598-020-60714-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of significant gene biomarkers of low back pain caused by changes in the osmotic pressure of nucleus pulposus cells

Abstract: The incidence of intervertebral disc (IVD) degeneration disease, caused by changes in the osmotic pressure of nucleus pulposus (NP) cells, increases with age. In general, low back pain is associated with IVD degeneration. However, the mechanism and molecular target of low back pain have not been elucidated, and there are no data suggesting specific biomarkers of low back pain. Therefore, the research aims to identify and verify the significant gene biomarkers of low back pain. The differentially expressed gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…HCAR2 has been implicated in macrophage recruitment and inflammatory responses and protein expression of hydroxycarboxylic acid receptor-2 (HCAR2) has been found in chondrocytes and peripheral nerve among other tissues [84][85][86] . Similarly, ADRA2C and SST have been found to be biomarkers in chronic pain for temporomandibular disorder and low back pain [87][88][89] . Although a study found low ADRA2C expression in cartilage, a recent report found a decrease in expression of this protein was associated with IVD degeneration 51,90 .…”
Section: Genes Associated With G Protein-coupled Receptorsmentioning
confidence: 97%
“…HCAR2 has been implicated in macrophage recruitment and inflammatory responses and protein expression of hydroxycarboxylic acid receptor-2 (HCAR2) has been found in chondrocytes and peripheral nerve among other tissues [84][85][86] . Similarly, ADRA2C and SST have been found to be biomarkers in chronic pain for temporomandibular disorder and low back pain [87][88][89] . Although a study found low ADRA2C expression in cartilage, a recent report found a decrease in expression of this protein was associated with IVD degeneration 51,90 .…”
Section: Genes Associated With G Protein-coupled Receptorsmentioning
confidence: 97%
“…A recent bioinformatic analysis identified significant gene biomarkers of LBP caused by changes in the osmotic pressure of NP cells, providing a reference for future in-depth research (Zhao et al, 2020).…”
Section: Intervertebral Discs Np Tissue Microenvironment (Fountain Of Youth)mentioning
confidence: 99%
“…Recently, in vitro studies have shown that static compression stress induces mitochondrial apoptosis in NP progenitor cells Yuan et al, 2018). Apart from the induction of apoptosis and senescence, stress stimuli seem to be critical for the normal functioning of progenitor cells (Hosseini et al, 2015;Kobayashi et al, 1989;Zhao et al, 2015). As an illustration of this, fluid-shear stress can give rise to overexpression of ECM components synthesised by AF progenitor cells (e.g.…”
Section: Influences Of Non-ecm Related Factors On Ivd Progenitor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 28 GPCR genes upregulated following CCI and CFA, several are known to be involved in abnormal generation of action potentials and altered pain thresholds (e.g., Gal1r, Gabbr2, Grm7, Gpr158, Chrm2, Chrm3, Cnr1, Oprl1, Oprm1, Mrgpre) as well as clinical pain conditions such as neuralgia (e.g., Htr2a, Htr2b, Ptger4, Mrgprx1) (Fig. 2D) [25][26][27][28][29][30][31][32][33][34][35]. Conversely, of the genes identified as transcriptional regulators, the number downregulated was 10-fold higher than the number upregulated (Fig.…”
Section: Shared Differential Expression Of Genes In CCI and Cfa Modelsmentioning
confidence: 99%